2020
DOI: 10.1111/ijd.15217
|View full text |Cite
|
Sign up to set email alerts
|

QuantiFERON TB‐gold conversion rate among psoriasis patients under biologics: a 9‐year retrospective study

Abstract: Background Tuberculosis (TB) screening is mandatory for psoriasis biologic treatment. However, evidences regarding TB screening results during biologic treatment are conflicting. Objectives The aim of this study is to evaluate the rate of QuantiFERON TB Gold test (QFT) conversion in psoriasis patients during biologics over time. Methods A 9‐year single center retrospective study was performed in order to evaluate the rate of QFT conversion in patients affected by moderate‐to‐severe plaque psoriasis under avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Parallel with previous real-world experience, we confirm the safety of SEC regarding TB activation among psoriasis patients [ 4 , 13 ]. In comparison, we recommend TB reevaluation in the first 3 months for patients treated with ADA in regions with high TB burden.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Parallel with previous real-world experience, we confirm the safety of SEC regarding TB activation among psoriasis patients [ 4 , 13 ]. In comparison, we recommend TB reevaluation in the first 3 months for patients treated with ADA in regions with high TB burden.…”
Section: Discussionsupporting
confidence: 87%
“…A long-term single-center retrospective study in the USA, an area with low TB risk, reported 1 LTBI case per 428 patient-years and no active TB cases among patients using biologic agents, including TNFi, IL-17i, and IL-12/23i [ 3 ]. In Italy, another area with low TB risk, a 9-year retrospective study indicated a 6.50% QFT conversion rate with no reports of active TB among psoriasis patients after a median of 34-month biological treatment [ 4 ]. Notably, the incidence of active TB is quite different in regions with median to high TB risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, further research is needed to continuously improve patients' condition. 15 Preclinical data and growing real-life evidence demonstrate the safety profile of Secukinumab in patients treated with systemic therapy. 7,8,13 To prevent high toxicity prophylaxis in patients with comorbidities, treatment strategy guidelines are awaited.…”
Section: Discussionmentioning
confidence: 99%